Exploring emotional experiences during Hajj: The role of social interactions - M. Hashim, Intan Hashimah; A. Hatta, Zulkarnain; Abdul Ghani, Noraida; Mohd. Mahudin, Nor Diana; Abdul Rahman, Shukran; Mat Saad, Zarina; Sulong, Jasni; Sehu Mohd, Zhooriyati; Ayob, Salahuddien; Shuib, Mohamad Arif; Ramli, Nurulhuda (2014)
This paper discusses how emotional experiences can be influenced by the social interactions during a spiritual context of Hajj.One of the components of emotion is the triggering events and the interpretation of the triggering events.This paper focuses on potential triggering events related to social interactions in the context of Hajj and debates on potential appraisals that are likely to be associated with these events.It can be argued that these ‘social’ events and appraisals associated with the events are likely to influence emotional experiences during Hajj.Dividing ‘social’ events into interactions in private and public spaces, this paper explores potential emotions in terms of types and intensity that can be elicited by each one of these events.This discussion is important to provide the background for any empirical studies on emotional experiences during Hajj.